Are We Family and Are We Treated as Family? Nonfamily Employees’ Perceptions of Justice in the Family Firm - Barnett, Tim; Kellermanns, Franz W. (Entrepreneurship Theory and Practice, 2006)
The importance of justice perceptions in fostering positive job attitudes and value–creating behaviors in organizations is well established in the literature. Despite this, only a handful of studies have addressed justice in family firms, and none have presented a theoretical model illustrating how nonfamily employees’ justice perceptions may be influenced by family involvement in family firms. Here, we suggest that the level of family influence impacts the justice perceptions of nonfamily employees primarily through its effect on the human resource (HR) practices within family firms. Specifically, we propose that low levels of family influence tend to have little impact on the fairness of HR practices, that moderate levels of family influence tend to have positive effects on the fairness of HR practices, and that high levels of family influence tend to have negative effects on the fairness of HR decision processes and outcomes. Accordingly, we present and provide a conceptual support for a model that outlines the proposed relationships among family influence, family firms’ HR practices, and the justice perceptions of nonfamily employees.